Nitrogen and sulfur conversion during pressurized pyrolysis under CO2 atmosphere in fluidized bed - Duan, Yuanqiang; Duan, Lunbo; Anthony, Edward J.; Zhao, Changsui (Elsevier, 2016)
Pressurized oxy-fuel combustion (POFC) is a promising technology for CO2 capture from coal-fired power plants, offering both high efficiency and a low penalty. However, the high partial pressure of CO2 in a POFC furnace has important impacts on fuel-N and fuel-S conversion during the coal pyrolysis process, and understanding this will help to achieve further control of SOx/NOx. In this study, coal pyrolysis experiments were conducted in a pressurized fluidized bed with the pressure range of 0.1–0.7 MPa under N2 and CO2 atmosphere. The gaseous products were monitored by a Fourier transform infrared spectroscopy analyzer (FTIR) and the char residue was characterized by an X-ray photoelectron spectroscopy (XPS) analyzer in order to acquire the species information for S-containing and N-containing compounds. Results show that the enrichment of CO2 in the local atmosphere enhances the fuel-N conversion to HCN in the pyrolysis process, which serves as a favorable precursor to N2O. The generation of HCN and NH3 increase simultaneously with the increase of overall pressure. SO2 concentration in the gaseous product is relatively low, and as the pressure increases, the concentration decreases slightly due to CO reduction of SO2 to COS. Sulfur content in the char decreases as the pressure goes from 0.1 MPa to 0.7 MPa indicating higher CO2 pressure accelerates the decomposition of sulfur compounds in the coal, which is further confirmed by the XPS results.
Keywords: Pressurized oxy-fuel combustion; Pyrolysis; CO2 atmosphere; Nitrogen conversion; Sulfur speciation